Vermicompost Buffering Capacity to Reduce Acidification of Pb and Cd Contaminated Inceptisols and Entisols - Muktamar, Zainal; Hermawan, Bandi; Wulandari, Wulandari; Prawito, Priyono; Sudjatmiko, Sigit; Setyowati, Nanik; Fahrurrozi, Fahrurrozi; Chozin, Mochammad (JOURNAL OF TROPICAL SOILS, 2021)
Contamination ofÂ  heavy metals on the soil leads to an increase in its acidity. Vermicompost application is commonly used to improve the properties of soil. The study was carried out to determine the reduction of the acidity in Pb and Cd contaminated soils under the application of vermicompost. Two laboratory experiments were set using Completely Randomized Design (CRD) with two factors. The first factor was soil samples, vis Inceptisols, and Entisols, and the second factor was the rates of vermicompost, consisted of 0, 5, 10, 15 g kg-1. The treatment combination was repeated three times. The soils were pretreated with 10 mg kg-1 Pb or Cd using Pb(NO3)2 and Cd(NO3)2. Three hundred kg soil sample was incorporated with vermicompost and placed in a 500 ml plastic bottle. The mixtures were incubated for eight weeks, and the moisture of the soil was maintained at field capacity. The acidity and soil temperature were monitored every week. The study indicated that Pb contaminated soil acidity increased to the sixth week of the incubation and decreased afterward. However, the acidity of Cd contaminated soil was consistently increased during the incubation. Treatment of vermicompost significantly lowered the acidity of both Pb and Cd contaminated soils. Contaminated Entisols had a higher response to the application of vermicompost than that of Inceptisols. This finding is significant in assessing acidity risk and possible management intervention for Pb and Cd contaminated soils.